(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Dalit movement in the social sphere appears to have emerged in roughly the final stages of the nineteenth century. From 1905, the nature of that movement was not only social but also ideological, applications, statements, articles, along with folk songs, pageants, poems, poetry, bhajans and qawwali programs were to take the form of literature. From all this, the spark of social awakening, inner consciousness and self-reflection was coming out from the social mind. It can be said that it was primarily of secondary nature as literature.